PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEMAMPUAN MENGATASI AMNESIA DIGITAL PADA SISWA MADRASAH ALIYAH - Fajariah, Nurul; Citriadin, Yudin; Fitriani, Fitriani (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the influence of transformational leadership style on students’ ability to overcome digital amnesia at Madrasah Aliyah in Sumbawa Barat. Using a quantitative correlational approach, the research involved a purposive sample of 40 students. The independent variable (X) is transformational leadership, measured through four indicators: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The dependent variable (Y) is the ability to overcome digital amnesia, assessed through indicators including technology dependency, memory ability, concentration, and deep learning. Data were collected using a five-point Likert scale questionnaire, which was tested for validity and reliability. Data analysis was conducted using descriptive statistics and multiple linear regression via the JASP software. The results indicate that transformational leadership has a positive and significant influence on students’ ability to cope with digital amnesia. This finding highlights the critical role of teachers' leadership in fostering independent learning and cognitive resilience in the digital era. The study recommends expanding the research to include more diverse schools and suggests a qualitative approach for deeper exploration in future research.